Analysis of energy consumption characteristics and fracture characteristics of moraine grouting solidified body under uniaxial compression - Li, Zheng-rong; Jiang, Ming-gui; Feng, Xing-long; Wang, Shao-yong; Zeng, Qing-tian; Chen, Chong; Liu, Wen-lian; Sun, Wei (Frontiers in Earth Science, 2023)
Glacial movement causes massive accumulation of fine-grained moraine, which often induces slope instability and moraine debris flow, and other geological hazards under raining and ice-snow melting effects. The modified phosphoric acid-water glass slurry was used for grouting and curing moraine, and the influencing law of water glass Baume degree and curing age on energy consumption characteristics and fracture properties of the grout-cured body of moraine by uniaxial compression test was analyzed. The results showed that the gel time of phosphoric acid-water glass slurry increased with increasing phosphoric acid addition and had a mutation phenomenon, and the gel time increased linearly with increasing phosphoric acid addition before the mutation; the compressive strength, pre-peak total energy, pre-peak elastic energy, pre-peak dissipative energy, elastic energy density, dissipative energy density, and pre-peak fracture toughness of the moraine curing body at same curing age are linearly increasing with the increase of water glass Baume degree by 46%-218%; the compressive strength, pre-peak elastic energy, and pre-peak elastic energy density of the moraine curing body increasing with the curing age but with different increases, growing slowly from 3 d to 7 d and growing rapidly from 7 d to 14 d. Through regression analysis of the test results, the fracture toughness calculation formula is derived from an energy perspective, and its research results have significant implications for moraine strata grouting reinforcement and glacial debris flow disaster prevention and control.